2014
DOI: 10.1021/am502743z
|View full text |Cite
|
Sign up to set email alerts
|

Confined Multiple Enzymatic (Cascade) Reactions within Poly(dopamine)-based Capsosomes

Abstract: The design of compartmentalized carriers as artificial cells is envisioned to be an efficient tool with potential applications in the biomedical field. The advent of this area has witnessed the assembly of functional, bioinspired systems attempting to tackle challenges in cell mimicry by encapsulating multiple compartments and performing controlled encapsulated enzymatic catalysis. Although capsosomes, which consist of liposomes embedded within a polymeric carrier capsule, are among the most advanced systems, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
90
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 79 publications
(93 citation statements)
references
References 69 publications
3
90
0
Order By: Relevance
“…The homogenous fluorescence, due to the presence of PLL F , confirmed that the PDA layer was thin enough to not entirely block the fluorescence emission. This aspect was important since we have prior observed that thick layers of PDA could entirely hinder the visualization of fluorescently labeled underlying layers . Furthermore, the particles remained well dispersed without aggregation, which was also supported when considering the flow cytometry histogram using particles suspended in HEPES 2 buffer (Figure c).…”
Section: Resultssupporting
confidence: 63%
See 1 more Smart Citation
“…The homogenous fluorescence, due to the presence of PLL F , confirmed that the PDA layer was thin enough to not entirely block the fluorescence emission. This aspect was important since we have prior observed that thick layers of PDA could entirely hinder the visualization of fluorescently labeled underlying layers . Furthermore, the particles remained well dispersed without aggregation, which was also supported when considering the flow cytometry histogram using particles suspended in HEPES 2 buffer (Figure c).…”
Section: Resultssupporting
confidence: 63%
“…Subcompartmentalized systems have been fabricated using predominantly a combination of liposomes, polymersomes, and polymer capsules as building blocks . Among the most advanced approaches are polymersomes in polymersomes and capsosomes, liposomes within polymer carrier capsules, including the demonstration of encapsulated enzymatic cascade reactions as the most complex functionality in both cases. Janus microreactors, toward the mimicry of the polarity of cells, were recently reported .…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, we have reported the trapping of structurally intact liposomes in PDA-based films on planar [16b][17c] and colloidal substrates. [18] Recently, microneedles coated with a liposome-containing film were successful used in vivo toward non-invasive vaccine delivery applications by loading the liposomes with a protein antigen. [19] However, detailed fundamental insight into the interaction between liposome-containing films and adhering cells remains scares.…”
Section: Introductionmentioning
confidence: 99%
“…The combination of several enzymatic transformations in concurrent onepot processes (multi-enzymatic cascade reactions) also plays an important role in biotechnology and modern synthetic chemistry [238,239]. In this context, attempts are also made to establish simple model systems for mimicking metabolism-like substrate transformations using multiple enzymatic cascade reactions in chemical environments resembling artificial cell structures [240].…”
Section: Reaction Cascades: Towards Metabolic Pathwaysmentioning
confidence: 99%